Inferring genetic diversity and population structure of India’s National Teak (Tectona grandis L.f.) Germplasm Bank - Mohammad, Naseer; Dahayat, Ankur; Pardhi, Yogesh; Rajkumar, Muthu; Ansari, Shamim Akhtar; Shirin, Fatima (Genetic resources and crop evolution, 2022)
Teak ( Tectona grandis L.f.) is a valuable tropical timber species native to South and Southeast Asia. In this study, we carried out a genetic diversity analysis among 238 accessions from 11 populations (representing eleven states) maintained in National Teak Germplasm Bank (NTGB) using SSR markers. Analysis of molecular variance (AMOVA) showed variations of 85% within and 15% among populations. Estimates of total number of alleles, nei’s gene diversity ( h ) and shannon’s information index ( I ) showed existence of high genetic variation between geographical regions. Accessions from Karnataka ( h = 0.855, I = 2.12) and Odisha ( h = 0.858, I = 2.11) exhibited the higher Nei’s gene diversity and Shannon's information index followed by accessions of Maharashtra and Tamil Nadu. The entire collections were clustered into two groups, confirmed by Bayesian model-based structure analysis. An analysis of population Q matrix revealed that the proportion of membership for few accessions were not distinct. Accessions from Odisha, Madhya Pradesh, Uttar Pradesh and Gujarat constituted one cluster whereas, Tamil Nadu & Kerala formed second cluster. Accessions from Andhra Pradesh, Karnataka and Maharashtra were found to be an admixture of both clusters. The influence of human and environmental factors might have played a major role in formation of a transition group. Possible reasons for the high genetic diversity and heterozygosity within this species are discussed and our results have firmly established that introduction of genetic materials from country-wide sources with larger sample size may broaden the genetic base and strategy of conservation programme at NTBG.